Designing Spelling Bee Game Through Scrabble For Junior High School - Luluk Choirun Nisak Nur; Siti Saudah; Yuyun Bahtiar (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
English is the language of media communication and the language of interaction with other people in the world. Students need creative and innovative learning products, especially to help students learn spelling and pronunciation. The purpose of this research is to design learning media as a tool for the teaching and learning process of students using the spelling bee game on spelling skills in speaking English. This study uses the R&D research and Development method with the ADDIE research model (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SMP DU 5 Jombang. The research subjects were 15 students. In this study, the data was collected using a questionnaire, while the data was collected using a qualitative descriptive technique. The results of this study get a total value of 3.5 for media validation and get a total value of 4.06 for material validation, with the category of